A Simple Method for the Prediction of the Detonation Performances of Metal-Containing Explosives - Wang, Yuan; Zhang, Jichuan; Su, Hui; Li, Shenghua; Zhang, Shaowen; Pang, Siping (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2014)
Accurate prediction to the detonation performances of different kinds of energetic materials has attracted significant attention in the area of high energy density materials (HEDMs). A common approach for the estimation of CHNO explosives is the Kamlet–Jacobs (K-J) equation. However, with the development of energetic materials, the components of explosives are no longer restricted to CHNO elements. In this study, we have extended the K-J equation to the calculation of certain metal-containing explosives. A new empirical method, in which metal elements are assumed to form metallic oxides, has been developed on the basis of the largest exothermic principle. In this method, metal oxides can be deemed as inert solids that release heat other than gases. To evaluate the prediction accuracy of new method, a commercial program EXPLO5 has been employed for the calculation. The difference involved in the ways of treating products has been taken into account, and the detonation parameters from two methods were subject to close comparison. The results suggest that the mean absolute values (MAVs) of relative deviation for detonation velocity (D) and detonation pressure (P) are less than 5%. Overall, this new method has exhibited excellent accuracy and simplicity, affording an efficient way to estimate the performance of explosives without relying on sophisticated computer programs. Therefore, it will be helpful in designing and synthesizing new metallic energetic compounds.